2008
DOI: 10.1002/ffj.1882
|View full text |Cite
|
Sign up to set email alerts
|

Fumigant antifungal activity of plant essential oils and components from West Indian bay (Pimenta racemosa) and thyme (Thymus vulgaris) oils against two phytopathogenic fungi

Abstract: Commercial plant essential oils obtained from 26 plant species were tested for their antifungal activity against Phytophthora cactorum and Cryponectria parasitica. Good antifungal activity against P. cactorum was achieved with the essential oil derived from thyme (Thymus vulgaris) and bay (Pimenta racemosa) at 28 × 10 -3 mg/ml air concentration. Inhibition rates of bay and red thyme were 69.1% and 100%, respectively, at 28 × 10 -3 mg/ml air concentration. In a test with C. parasitica, the inhibition rates of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 15 publications
2
27
0
1
Order By: Relevance
“…Compared with other fungal species, our results are in agreement with Kim, Lee, Lee, Shin, and Park (2008), who reported a higher antifungal activity of isoeugenol respect to eugenol and of carvacrol respect to thymol on Phytophthora cactorum and Cryponectria parasítica, and also with López-Malo, Palou, León-Cruz, Stella, and Alzamor (2005), who demonstrated the following order of activities of phenolic components on the growth of Aspergillus flavus: carvacrolethymol > eugenol > vanillin. These authors concluded that the ability of different natural compounds to inhibit the (1)) applied to eight natural phenolic compounds.…”
Section: Discussionsupporting
confidence: 95%
“…Compared with other fungal species, our results are in agreement with Kim, Lee, Lee, Shin, and Park (2008), who reported a higher antifungal activity of isoeugenol respect to eugenol and of carvacrol respect to thymol on Phytophthora cactorum and Cryponectria parasítica, and also with López-Malo, Palou, León-Cruz, Stella, and Alzamor (2005), who demonstrated the following order of activities of phenolic components on the growth of Aspergillus flavus: carvacrolethymol > eugenol > vanillin. These authors concluded that the ability of different natural compounds to inhibit the (1)) applied to eight natural phenolic compounds.…”
Section: Discussionsupporting
confidence: 95%
“…GC and GC‐MS analyses of cinnamon, geranium, cumin, thyme, basil and lemongrass essential oils revealed that the main components of these oils were cinnamaldehyde (80.4%), citronellol (41.6%), cuminaldehyde (46.9%), thymol (39.8%), linalool (50.0%) and citronellal (20.8%), respectively. Several prior studies have demonstrated the high antimicrobial activity of cinnamaldehyde, citronellol, cuminaldehyde, thymol, linalool and citronellal in different phytopathogens . In addition, it is also possible that minor components of the various essential oils, such as γ ‐terpinene in cumin, carvacrol in thyme, β ‐caryophyllene and oestragole in basil, and so on, may be involved in exerting antimicrobial activity, acting synergistically with other active components of the essential oil, as was evident in previous studies .…”
Section: Discussionmentioning
confidence: 92%
“…Among the various alternatives are plant-derived compounds such as essential oils (EOs). EOs are natural, volatile, complex compounds known for their antibacterial, antifungal, antiviral, antioxidant and medicinal properties (Kim et al, 2008;Rhoades et al, 2013;Gilling et al, 2014;Talibi et al, 2014;Sivakumar and Bautista-Banos, 2014). The development of resistant strains of fungi against essential oils may be less likely as it is for many synthetic fungicides because several active components are often present in the EOs and synergistic interactions may exist between the different components of the oils (Tripathi and Dubey, 2003;Tripathi et al, 2004).…”
Section: Introductionmentioning
confidence: 99%